2003
DOI: 10.1029/2002gl016849
|View full text |Cite
|
Sign up to set email alerts
|

The zonal currents and transports at 35°W in the tropical Atlantic

Abstract: [1] The total of 13 existing cross-equatorial shipboard current profiling sections taken during the WOCE period between 1990 and 2002 along 35°W are used to determine the mean meridional structure of the zonal top-to-bottom circulation between the Brazilian coast, near 5°S, and 5°N and to estimate mean transports of the individual identified shallow, intermediate and deep current branches. One of the results is that, on the equator, a mean westward Equatorial Intermediate Current below the Equatorial Undercurr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
113
3

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 95 publications
(133 citation statements)
references
References 10 publications
(17 reference statements)
17
113
3
Order By: Relevance
“…[55] Our results also suggest that the EUC at 10°W is rather located under the thermocline, contrarily to the western EUC always found within the thermocline [Schott et al, 2003;Brandt et al, 2006]. Our results show a strong semiannual variability of the EUC transport and indicate that the hydrological structure varies strongly above and beneath the EUC velocity core.…”
Section: Discussionsupporting
confidence: 64%
See 4 more Smart Citations
“…[55] Our results also suggest that the EUC at 10°W is rather located under the thermocline, contrarily to the western EUC always found within the thermocline [Schott et al, 2003;Brandt et al, 2006]. Our results show a strong semiannual variability of the EUC transport and indicate that the hydrological structure varies strongly above and beneath the EUC velocity core.…”
Section: Discussionsupporting
confidence: 64%
“…These results suggest that, while the EUC transport significantly decreases from 35°W to 26°W and loses about 6 Sv, it decreases only modestly farther east, losing 1.7 Sv between 26°W and 10°W. From the 12.1 Sv EUC total transport, 0.4 Sv occurs in the surface layer, i.e., above s q = 24.5 (as previously defined by Schott et al [2003] and Brandt et al [2006]), and 11.7 Sv in the thermocline as follows: 2.5 Sv in the upper thermocline, 8.3 Sv in the lower thermocline layer, and 0.9 Sv in the deep thermocline above 250 m depth (Table 2). Brandt et al [2006] found at 26°W an EUC transport of 3.1 Sv above s q = 24.5 and 10.7 Sv below.…”
Section: Mean Flow At 10°wmentioning
confidence: 67%
See 3 more Smart Citations